Quantum Dot Luminescent Solar Concentrator: Optimization of Concentration and Thickness - RAFIEE, MEHRAN; Chandra, Subhash; Ahmed, Hind; McCormack, Sarah J. (My University, 2017)
The absorption coefficient of a Luminescent Solar Concentrator (LSC) can non-linearly affect the total optical efficiency (η_opt) and solar concentration ratio (C_P) of the device. Absorption is determined by two critical design parameters; the concentration of the luminescent material and the thickness of LSC plate. This paper presents a theoretical approach using a mathematical model based on a Ray Tracing algorithm to optimize these parameters to obtain the best LSC configuration design. A 60 × 60 × 3 mm LSC of CdSe/ZnS quantum dots (QDs) doped in epoxy resin was modelled and the model results were validated by comparing them to experimental results. To achieve the optimum thickness and luminescent material concentration of the LSC, a sensitivity analysis was carried out to predict the behavior of the LSC under different solar radiation. The LSC optical efficiency under standard AM1.5 global solar radiation was found to have reached a maximum (3.6%) at QD concentration of 0.55 wt%. Above this concentration, the optical efficiency was found to decrease due to re-absorption losses. Then, the thickness of the LSC was varied from 0.5 to 30 mm while the QD concentration was kept constant at the optimum (i.e. 0.55 wt%). Under these circumstances, the total optical efficiency has been observed to increase from 1.2% to 13.2% while the C_P was significantly decreased from 1.19 to 0.22 due to a decrease in the geometric gain
33rd European PV Solar Energy Conference and Exhibitions (EU PVSEC 2017)
Keywords: Luminescent solar concentrator; Ray tracing; Modeling; Concentration; Thickness; Quantum dot; Emission; Absorption; Sensitivity analysis; Creative Technologies